Variation of cloudiness in the mountain region on the example of the Sudetes - Szyga-Pluta, Katarzyna (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2017)
The purpose of the study is to present a comparison of cloudiness at different levels of a mountain region and to emphasize the specific characteristics of cloud cover observed in valleys and on mountain summits, based on the example of the Sudetes. The analysis is based on cloudiness observations made in Jelenia Góra and on Mt Śnieżka in the years 1971-2015. The results obtained in the study demonstrate that the average cloudiness generally increases with altitude in the Sudetes. However, in the colder half of the year, in anticyclonic weather and thermal inversion conditions, this system may be inverted. There are more cloudless and clear days on average in the valleys and more overcast and cloudy days recorded at the tops of the Sudetes. The annual cloud cover amount is similar, due to atmospheric circulation. The diurnal pattern varies as an effect of the influence of local conditions. The increase in cloudiness during the period from 1971-2015 is more significant in Jelenia Góra than on Śnieżka.
Keywords: cloudiness; mountain; valley; Jelenia Góra; Śnieżka; Sudetes